Perioperative Kidney Injury Principles of Risk Assessment, Diagnosis and Treatment - Thakar, Charuhas V.; Thakar, Charuhas V.; Parikh, Chirag R.; Parikh, Chirag R. (Springer New York : Imprint: Springer, 2015)
The kidneys participate in all vital processes of the body to maintain overall homeostasis and health. When kidneys are injured during surgical interventions, metabolic and hemodynamic control is disrupted, leading to dysfunction associated with greater mortality, length of hospital stay, and cost. Peri-operative Kidney Injury presents the epidemiology, risk factors, diagnosis, treatment, and outcomes associated with kidney injury during the peri-operative period. Concepts and principles of care to prevent kidney complications during surgical procedures are provided to equip health care professionals along with strategies to manage acute kidney injury and associated challenges when they occur. Chapters detail diverse surgical settings, ranging from the more common, such as abdominal, cardiac, and vascular surgeries, to the intricately complex, including the use of the left ventricular assist device and organ transplants. This practical and comprehensive text blends the evidence-based standards of care with cutting edge advances in the field, while also providing the reader with a peek into innovations on the horizon.